2020
DOI: 10.1371/journal.pone.0234437
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of spider species in a mosaic montane grassland landscape

Abstract: Gene flow and genetic variation were examined within and among populations of five of the most common spider species in shrublands of the mountainous Golden Gate Highlands National Park (GGHNP), South Africa. These species included three active hunters, Dendryphantes purcelli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 105 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Several studies found ballooning dispersal behaviour to be related to small body sizes (Dean & Sterling, 1985;Greenstone et al, 1987) and vegetation structure (Blandenier, 2009). Dispersal by ballooning is associated with high gene flow and weak population structure, even in mountainous landscapes (Botham et al, 2020) and can influence the occurrence and the composition of spider communities (Bonte et al, 2003a(Bonte et al, , 2004Jiménez-Valverde et al, 2010). In contrast, the level of habitat specialisation seems to be negatively related to the ballooning ability (Bonte et al, 2003b), as a high tendency to balloon increases the risk of reaching potential unsuitable habitats and therefore should increase population structuring.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found ballooning dispersal behaviour to be related to small body sizes (Dean & Sterling, 1985;Greenstone et al, 1987) and vegetation structure (Blandenier, 2009). Dispersal by ballooning is associated with high gene flow and weak population structure, even in mountainous landscapes (Botham et al, 2020) and can influence the occurrence and the composition of spider communities (Bonte et al, 2003a(Bonte et al, , 2004Jiménez-Valverde et al, 2010). In contrast, the level of habitat specialisation seems to be negatively related to the ballooning ability (Bonte et al, 2003b), as a high tendency to balloon increases the risk of reaching potential unsuitable habitats and therefore should increase population structuring.…”
Section: Introductionmentioning
confidence: 99%
“…We can conclude that ballooning is the key factor affecting expansion potential in spiders, in its turn associated with producing cobwebs; hence, cobweb building, which independently evolved in several clades of spiders (Fernández et al., 2014 ), is an important general adaptation, not only for saving energy while catching prey (Eberhard, 1990 for review) but also increasing dispersal rates on short (Botham et al., 2020 ), middle (Domènech et al., 2022 ), as well as on very large distances (this study), and hence, the effective size of spider populations.…”
Section: Discussionmentioning
confidence: 97%